Socio-economic Impact Assessment of Floods in District-13 of Kabul City - Hashimi, Sayed Kazem; Sahak, Kawon; Mushwani, Hayatullah (Journal of Natural Sciences – Kabul University, 2022)
Floods cause significant social, economic, and environmental damage in our country, and Kabul city is no exception. This study was conducted to assess the socio-economic vulnerability of residents in District-13 of Kabul city. A validated questionnaire was used to collect data from the study area. The results indicate that floods primarily occur due to climatic conditions during the spring season. The study also revealed that 37% of the impacts were economic, 33% were social, and 30% were environmental. The main impacts identified were destruction of roads and passages (72%), blockage of alleys and roads (68%), and mental health disorders (67%). In conclusion, effective public awareness programs, management plans, early warning systems, and planned urban development can help minimize the socio-economic impacts of floods in the area.